Formulation and characterization of solid lipid nanoparticles, nanostructured lipid carriers and nanoemulsion of lornoxicam for transdermal delivery - Gönüllü Ümit; Üner Melike; Yener Gülgün; Karaman Ecem Fatma; Aydoğmuş Zeynep (Acta Pharmaceutica)
Solid lipid nanoparticles (SLN), nanostructured lipid carriers (NLC) and nanoemulsion (NE) of lornoxicam (LRX) were prepared for the treatment of painful and inflammatory conditions of the skin. Compritol® 888 ATO, Lanette® O and oleic acid were used as solid and liquid lipids. SLN, NLC and NE were found physically stable at various temperatures for 6 months. Case I diffusional drug release was detected as the dominant mechanism indicating Fickian drug diffusion from nanoparticles and nanoemulsion. The highest rate of drug penetration through rat skin was obtained with NE followed by NLC, SLN and a gel formulation. Nanoformulations significantly increased drug penetration through rat skin compared to the gel (p < 0.05). Thus, SLN, NLC and NE of LRX can be suggested for relieving painful and inflammatory conditions of the skin